Rain man Level 3 - Fleischer, Leonore; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2008)
Charlie Babbitt thinks he will get a lot of money when his father dies. However the money goes to someone he doesn't know - a man who lives in hospital and is the brother Charlie never knew he had. The two meet and so starts a surprising new life for both of them.
Based on a screenplay by Ronald Bass and Barry Morrow and a story by Barry Morrow
Keywords: Tham khảo